Strategy for the biotransformation of fermented palm oil mill effluent into biodegradable polyhydroxyalkanoates by activated sludge - Lee, W.S.; Chua, A.S.M.; Yeoh, H.K.; Nittami, T.; Ngoh, G.C. (Elsevier, 2015)
Management of wastewater by resource recovery approach allows the transformation of wastewater into valuable resources. This work examines the biotransformation of fermented palm oil mill effluent (POME) into biodegradable plastics - polyhydroxyalkanoates (PHA) - through cultivation and enrichment of PHA-accumulating organisms in activated sludge and the subsequent production of PHA by the cultivated sludge. Enrichment of PHA-accumulating organisms via aerobic dynamic feeding process was effective and had significantly enhanced the PHA storage capacity of the sludge (wt PHA per sludge dry weight) from 4 wt (seed sludge) to 40-64 wt (sludge cultivated for 50 days and more). The cultivated sludge comprised of 42 +/- 12 Betaproteobacteria, 35 +/- 7 Alphaproteobacteria, and 13 4 Gammaproteobacteria, as estimated by fluorescent in situ hybridization. The influence of pH (4.5 in the absence of pH control; and pH 7,8 and 9) on the production of PHA by the cultivated sludge was subsequently investigated. Neutral pH was the most favorable for PHA production, resulting in a PHA content of 64 wt in 8 h. The PHA produced was made up of 77 mol 3-hydroxybutyrate and 23 mol 3-hydroxyvalerate. These findings signify that the combination of fermented POME and activated sludge offers an alternative to the palm oil and the plastics industries for a more sustainable POME management and an economical PHA production route. (C) 2015 Elsevier B.V. All rights reserved.